Microbes as carbendazim degraders: opportunity and challenge - Zhou, Yi; Wang, Tianyue; Wang, Liping; Wang, Pengfei; Chen, Feiyu; Bhatt, Pankaj; Chen, Shaohua; Cui, Xiuming; Yang, Ye; Zhang, Wenping (Frontiers in Microbiology, 2024)
Carbendazim (methyl benzimidazol-2-ylcarbamate, CBZ) is a systemic benzimidazole carbamate fungicide and can be used to control a wide range of fungal diseases caused by Ascomycetes, Basidiomycetes and Deuteromycetes. It is widely used in horticulture, forestry, agriculture, preservation and gardening due to its broad spectrum and leads to its accumulation in soil and water environmental systems, which may eventually pose a potential threat to non-target organisms through the ecological chain. Therefore, the removal of carbendazim residues from the environment is an urgent problem. Currently, a number of physical and chemical treatments are effective in degrading carbendazim. As a green and efficient strategy, microbial technology has the potential to degrade carbendazim into non-toxic and environmentally acceptable metabolites, which in turn can dissipate carbendazim from the contaminated environment. To date, a number of carbendazim-degrading microbes have been isolated and reported, including, but not limited to, Bacillus, Pseudomonas, Rhodococcus, Sphingomonas, and Aeromonas. Notably, the common degradation property shared by all strains was their ability to hydrolyze carbendazim to 2-aminobenzimidazole (2-AB). The complete mineralization of the degradation products is mainly dependent on the cleavage of the imidazole and benzene rings.Additionally, the currently reported genes for carbendazim degradation are MheI and CbmA, which are responsible for breaking the ester and amide bonds, respectively. This paper reviews the toxicity, microbial degradation of carbendazim, and bioremediation techniques for carbendazim-contaminated environments. This not only summarizes and enriches the theoretical basis of microbial degradation of carbendazim, but also provides practical guidance for bioremediation of carbendazimcontaminated residues in the environment.